Toxic Problems In Students At School (Case Study of PAI Implementation in Attitude Aspect at UNESA 2 Labschool Junior High School) - Aksin Mubarroh (International Journal of Religion and Social Community, 2023)
This article discusses Toxic in Learners at School. The main finding of this article is that so far, Toxic has become a habit of Learners both at school, home and in the surrounding environment. The main factors for the spread of Toxic behavior in the student environment are through association, games, imitating and seeing the behavior of idol characters on video platform channels. While the solution offered by the Islamic Religious Education Teacher is to consciously accustom students to get used to self-control and stay away from Toxic behavior, read istiqfar every time they say Toxic sentences and get used to students to supervise and advise each other if there are other students who say Toxic sentences at school. Through this habituation, based on observations made in the field, the results of reducing Toxic behavior at school were obtained. Therefore, it is recommended that the role of the involvement of all school components to jointly control and suppress Toxic behavior that occurs at school.